Pathological Consequences of Sequence Duplications in the Human Genome - Mazzarella, Richard; Schlessinger, David

(untitled) (Genome Research, 1998)
As large-scale sequencing accumulates momentum, an increasing number of instances are being revealed in which genes or other relatively rare sequences are duplicated, either in tandem or at nearby locations. Such duplications are a source of considerable polymorphism in populations, and also increase the evolutionary possibilities for the coregulation of juxtaposed sequences. As a further consequence, they promote inversions and deletions that are responsible for significant inherited pathology. Here we review known examples of genomic duplications present on the human X chromosome and autosomes.